Sistem Monitoring Kehadiran Perkuliahan Menggunakan Face Detection Dengan Algoritma Viola Jones - Fachmi, Zul; Sudarma, Made; Jasa, Lie (Majalah Ilmiah Teknologi Elektro, 2019)
Presence of lectures is an important factors to take the final exam. It is necessary to have a presence system with computer vision technology that is capable to handling problems manually. Computer vision technology used is face detection and recognition in order to monitor attendance data system. The face detection process in this study uses the Viola-Jones algorithm, and this algorithm has four stages, namely Haar Like Feature, Integral Image, Adaboost learning and Cascade classifier. The results of this study Viola-Jones algorithm successfully applied to the face detection process and in the face recognition process using the KNN (K-Nearest Neighbor) method with an accuracy rate of 94.79%.